(untitled) (Global Journals of Research in Engineering, 2011)
The broadband behavior of the fractal Sierpinski#x2019;s gasket antenna is described in this paper. A stacked microstrip gasket antenna at iterations level three for C-band application is designed and simulated on IE3D software. The feeding technique used is transformer feed. Simulated results shows that this antenna has three resonant frequencies of gain of order 5dBi with a bandwidth of 1.64GHz and percentage bandwidth of 48.2 which empower it as a broadband antenna.